Manipulation of host cells by Chlamydia trachomatis: function and subcellular localization of an inclusion membrane protein - Luís, Maria Silva Filipe Pequito (2024)
Chlamydia trachomatis is an obligate intracellular bacterial pathogen that causes ocular and genital infections of major burden worldwide. Once inside host cells, C. trachomatis resides within a specialized vacuole, known as an inclusion. From within the inclusion, C. trachomatis utilizes a type III secretion system to transport effector proteins into the host cell which subvert many cellular processes. Among these effectors, there is a large group, termed Incs, which insert at the inclusion membrane. In this work, to advance the understanding on molecular and cellular mechanisms underlying C. trachomatis virulence, we focused on characterizing the role of Inc CT288/CTL0540 (renamed IncM). We showed that IncM is conserved among mostChlamydia species, highlighting its evolutionary significance. At a functional level, we revealed that IncM participates in the ability of Chlamydia to inhibit host cytokinesis, dislocate centrosomes, and redistribute the Golgi complex around the inclusion. IncM also showed to contribute to the maintenance of the inclusion morphology and stability, and the circularity of IncM-deficient inclusions was specifically sensitive to microtubule depolymerization. Overall, these findings suggested that IncM may exert its effector function by acting directly or indirectly on host microtubules. We also found an intriguing role of the promoter used for inc gene expression regarding the exact localization of IncM and other Incs (IncD and InaC). This led us to identify three novel bona fide Incs (CT195, CT214, and CT484). In summary, by detailing the function of IncM, this work increased the understanding of how C. trachomatis manipulates host cells through its effectors. It also suggests future studies on how IncM acts on host microtubules, how the novel identified Incs function, and how gene expression within the chlamydiae can dictate an exact protein localization at the inclusion membrane.